New flow boiling frictional pressure drop multipliers for smooth and microfin tubes - Celen, Ali; Dalkilic, Ahmet Selim (WALTER DE GRUYTER GMBH, 2022)
The accurate calculation of pressure drop of evaporators/condensers are crucial and related with the pumping power, performance coefficient and energy consumption in a refrigeration equipment. This work aligns frictional pressure drop models/correlations with the experimental outcomes of boiling pressure drop of R134a in horizontal smooth and microfin copper tubes with equivalent outer diameter of 9.52 mm. The pressure drop through the test tube is obtained with a differential pressure transducer directly. Effective parameters are specified for smooth and microfin tubes and the most compatible models/correlations, 12 for smooth tubes and 9 for microfin ones, are determined accurately in relation to the consequences of investigation during intermittent and annular flow regime. Moreover, new two-phase multipliers have been developed by using regression analyses of 182 data points based on Lockhart-Martinelli parameter for each test tubes separately, and their predictability are found to be better than others in the literature as novel ones. Average errors of the developed empirical correlations are 11% for smooth and for 7% for microfin tubes. Finally, the measured data is given for the validation issues of researchers who can benefit from most of the investigated pressure drop models with tolerable accuracy regarding with their HEX design analyses.
Keywords: boiling; friction factor; microfin tube; pressure drop; two-phase flow; HEAT-TRANSFER CHARACTERISTICS; VOID FRACTION MODELS; VERTICAL DOWNWARD FLOW; 2-PHASE FLOW; NUMERICAL CORRELATION; TRANSFER COEFFICIENT; AIR-WATER; CONDENSATION; R134A; REFRIGERANTS; Nuclear Science & Technology